1983
DOI: 10.1093/oxfordjournals.aje.a113537
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Incidence of Hypertension in College Alumni

Abstract: In a study population of 14,998 Harvard male alumni, 681 hypertensives were first diagnosed during a 6-10-year follow-up beginning 16-50 years after college entrance. The study comprised 105,662 man-years of observation of these men who had entered college in 1916-1950, and who were followed from 1962 or 1966 to 1972. Presence or absence of a background of collegiate sports did not influence risk of hypertension in this study population, nor did stair-climbing, walking, or light sports play by alumni. But, alu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
219
0
22

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(254 citation statements)
references
References 0 publications
13
219
0
22
Order By: Relevance
“…Paffenbarger et al (31), for example, showed that among 14,998 Harvard male alumni that initially presented without hypertension in 1962 or 1966, 681 (5%) developed hypertension by 1972, with those not engaging in vigorous sporting activities at 35% greater risk of developing hypertension than those who did. Regular physical exercise, especially aerobic exercise, has therefore often been recommended for the prevention, treatment, and control of hypertension (36,41).…”
Section: Introductionmentioning
confidence: 99%
“…Paffenbarger et al (31), for example, showed that among 14,998 Harvard male alumni that initially presented without hypertension in 1962 or 1966, 681 (5%) developed hypertension by 1972, with those not engaging in vigorous sporting activities at 35% greater risk of developing hypertension than those who did. Regular physical exercise, especially aerobic exercise, has therefore often been recommended for the prevention, treatment, and control of hypertension (36,41).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In the past three decades, a number of studies have reported blood pressure (BP) reductions in hypertensives undergoing a regular program of aerobic exercise.5-31 Consequently, various reviews32-35 and the Joint National Committee on Detection, Evaluation, and Treatment of High Blood Pressure36 have concluded that exercise can be beneficial in the management of hypertension but that more studies are needed because there is still a paucity of adequately controlled randomized studies. Importantly, few of the studies conducted to date used a control group of hypertensives, and none used a credible attention control or placebo treatment control group of hypertensive subjects.…”
mentioning
confidence: 99%
“…There are several studies realized on children and adolescents in which has been studied the relation between blood pressure and cardiorespiratory fitness (Paffenbarger et al 1983;Hansen et al, 1991). Hansen et al explored the impact of the aerobic training on blood pressure for obese children (Hansen et al, 1991).…”
Section: Jpes ®mentioning
confidence: 99%
“…Biological risk factors for the occurrence of cardiovascular diseases track from childhood and adolescence into adulthood (Andersen 1996;Twisk et al, 1997). The low level of fitness is associated with an increased risk of high blood pressure for middle-aged men and women (Paffenbarger et al 1983;Blair et al, 1984). But there are many fewer researches which explain the etiological relationship between fitness and blood pressure for children and adolescents (Hagberg et al, 1983;Hagberg et al, 1994;Fraser et al, 1983).…”
Section: Introductionmentioning
confidence: 99%